2017
DOI: 10.1111/dsji.12132
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Improvement of Team Assignments: Using a Web‐Based Tool and the Plan‐Do‐Check‐Act Cycle in Design and Redesign

Abstract: The purpose of this brief is twofold. First, it describes a useful template for business instructors to improve teamwork assignment design and efficacy; and second, it provides an example of how to use data collected and analyzed from a Web‐based tool, Comprehensive Assessment of Team Member Effectiveness (CATME). Though CATME has been the subject of research regarding its impact on team effectiveness, less common is a clear description of its use for continuous improvement by instructors in the classroom. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The concept of kaizen is in turn supported by an emphasis in work standardization and real time experimentation (Spear and Bowen, 1999). Work standardization provides a solid baseline over which processes can be improved minimizing the risk of recurrence and experimentation following Deming's cycle of Plan-Do-Check-Act (Morgan and Stewart, 2017) provides the foundation for continuous, incremental improvement. Many of the lean tools and concepts are actionable at the shop floor level mainly by team members or team leaders, such as value stream mapping, standardized work documents or visual controls (Cottyn et al, 2011;Spear and Bowen, 1999).…”
Section: Changes In Communication Patternsmentioning
confidence: 99%
“…The concept of kaizen is in turn supported by an emphasis in work standardization and real time experimentation (Spear and Bowen, 1999). Work standardization provides a solid baseline over which processes can be improved minimizing the risk of recurrence and experimentation following Deming's cycle of Plan-Do-Check-Act (Morgan and Stewart, 2017) provides the foundation for continuous, incremental improvement. Many of the lean tools and concepts are actionable at the shop floor level mainly by team members or team leaders, such as value stream mapping, standardized work documents or visual controls (Cottyn et al, 2011;Spear and Bowen, 1999).…”
Section: Changes In Communication Patternsmentioning
confidence: 99%
“…Research in this stream citing Bacon et al (1999) describes the value of using online tools to assist with the creation of teams balanced by gender, race, disciplinary area, GPA (grade point average), and so on. (Jahanbakhsh, Fu, Karahalios, Marinov, & Bailey, 2017; Morgan & Stewart, 2017). These online tools have provided greater rationality to student assignment, consistent with Swaim and Henley (2017, JME ), and has resulted in better distribution of talents and backgrounds, and opportunities to hone conflict management skills (Oakley, Hanna, Kuzmyn, & Felder, 2007) within teams.…”
Section: Team Formation Policymentioning
confidence: 99%
“…Social loafing, which Bacon et al (1999) found to be a significant process variable contributing to negative team experiences, has continued to provide fertile ground for research. Beyond articles published in JME , techniques to reduce social loafing have been positively related to practices associated with team assignment (Brandyberry & Bakke, 2006; Pieterse & Thompson, 2010), team task structure (Morgan & Stewart, 2017), and characteristics of peer evaluation (Brooks & Ammons, 2003; Fellenz, 2006, JME ). Many of these research contributions articulate possible root causes behind free-riding behavior and advocate for its early detection and resolution (Hall & Buzwell, 2012).…”
Section: Structure Of the Team Assignmentmentioning
confidence: 99%
“…The purpose of this paper is to promote effective student teamwork by co-creating with students a virtual team classroom environment guided by the elaborated action design science research (eADSR) approach as detailed by Mullarkey and Hevner (2019). Invariably, researchers acknowledge the negative sentiment of students toward teams (Jasswall et al, 2010), in addition to the increased administrative overhead of grading and dealing with freeriders, social loafing and managing peer evaluations (Koppenhaver and Shrader, 2003;Morgan and Stewart, 2017). The preponderance of literature on student groups and teams features instructor-driven pedagogical interventions, inquiries, innovations and approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The 2020 National Association of Colleges and Employees Jobs Outlook related that the "ability to work in a team" is the second-highest-rated skill sought by employers (NACE, 2019), which remains unchanged from 2016 (Morgan and Stewart, 2017). Team skills remain essential as the team working environment continues to change considerably.…”
Section: Introductionmentioning
confidence: 99%